A Republic with a Royal Crown - The Historical Development of the Holy Crown Concept in the Hungarian Constitution - Szakats, Alexander (Victoria University of Wellington Law Review, 1997)
The idea of a Royal Crown personifying a state which is a Republic is an intriguing one. That is the situation of the Republic of Hungary. In this article, Professor Szakats traces the origins of the idea from the early days of Hungary through to its confirmation in 1989. The article also explores the nature and constitutional implications of the Crown as a legal person.